Nilai-Nilai Estetika Tari Panglukating Jiwa dalam Ritual Pangrupukan Tilem Sasih Kasanga Caka 1946 di Pura Bhuana Puka Tamansari Boyolali - Wahyuningsih; Santika, I Kadek Dwi; Astuti, Ni Luh Putu Wiardani (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This research examines the Panglukating Jiwa Dance as an effort to enhance creativity among the younger generation in appreciating and developing dance works. Many young people today have limited understanding of artistic works although art and religion are closely related in cultural practice. The Panglukating Jiwa Dance serves as a medium for exploring creativity in the arts within a religious and cultural context. This study focuses on the aesthetic values of the Panglukating Jiwa Dance performed in the Pangrupukan Tilem Sasih Kasanga ritual in 2024 at Pura Bhuana Puja Tamansari Boyolali. This study employs a qualitative descriptive method. The analysis covers the background of the dance creation, its form of presentation, and the aesthetic values contained in the Panglukating Jiwa Dance within the ritual context. The research applies Structural Functional Theory, particularly Talcott Parsons’ AGIL framework, and the aesthetic theory proposed by Djelantik. Data were obtained through observation, interviews, documentation, and literature review. The findings indicate that the creation of the Panglukating Jiwa Dance is influenced by community values, social norms, and environmental conditions. Its presentation reflects aesthetic elements including movement, makeup and costumes, floor patterns, musical accompaniment, properties, and lighting. The dance embodies cultural, religious, and economic values expressed through three aesthetic principles: unity and integrity, dominance or emphasis, and balance among supporting elements. Overall, the Panglukating Jiwa Dance functions not only as a ritual performance but also as an artistic expression that fosters creativity among the younger generation.